From lending to learning : the development and extension of public libraries - O'Beirne, Ronan (Chandos information professional series., 2010)
From Lending to Learning provides a theoretical overview and practical guide to the functional area of delivering learning services within public libraries. It traces the development of public library service delivery and critically appraises the inherent tension between offering an educational focused or leisure focused library. The current and future policy directions are explored against the backdrop of the emerging learning society. A general overview of recent developments in learning theory is followed by an insight into the learning landscape. The issues and practicalities of setting up a learning environment within a public library are dealt with in a clear and straightforward fashion. The book concludes with an assessment of the emerging Web 2.0 technologies and gives an insight into how the whole area of social networking might shape the future.